Self-efficacy and neurocognition may be related to coping responses in recent-onset schizophrenia - Ventura, Joseph; Nuechterlein, Keith H; Subotnik, Kenneth L; Green, Michael F; Gitlin, Michael J (Schizophrenia research, 2004)
Although stressful life events can trigger psychotic and depressive symptom exacerbation in schizophrenia, many patients who experience stressful events do not subsequently relapse. Models of vulnerability, stress, and protective factors in schizophrenia suggest that effective coping responses may serve as protective factors. Coping behavior, in turn, may be influenced by a schizophrenia patient's level of self-efficacy and neurocognitive functioning. Using the Coping Responses Inventory, we examined how 29 recent-onset schizophrenia outpatients and 24 demographically matched normal comparison subjects responded to a negative interpersonal life event. Approach oriented coping responses, such as “Think of different ways to deal with the problem” and “Make a plan of action and follow it,” were used significantly more often by normal subjects ( M=2.27) than by schizophrenia patients ( M=1.89; p<0.02). Among schizophrenia patients, greater use of approach, problem-focused coping strategies was associated with high self-efficacy ( r=0.55, p<0.01) and better performance on a measure of sustained attention emphasizing perceptual processing ( r=0.42, p<0.05). Multiple regression indicated that self-efficacy and sustained attention accounted for 56% of the variance in the use of problem-focused coping strategies by schizophrenia patients.